A critical evaluation of peripheral blood smear in the diagnosis of thalassemia syndrome - Sunarto, Sunarto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
The severe affected thalassemla syndrome Is common In Southeast Asian countries. Considering that the feature of its peripheral blood smear Is typical, this study was aimed at investigating the diagnostic value of the blood smear in thalassemia syndrome. Sixty five patients with severe anemia and splenomegaly who were admitted or came for follow up to Sardjito General Hospital in the period of 1996 and 1997 had been enrolled In this study. The peripheral blood smear was assessed, whether thalassemla or nonthalassemia, by two laboratory technicians, each of them read blindly each smear at two occasions with at least two weeks interval. The gold standard for diagnosis of thalassemla major was the evidence of increased HbA2 (>3,5% of total Hb) In both parents and for thalassemla-hemoglobin E disease was the increased HbA2 in one of the parents and the presence of HbE in the other. The measurements of HbA2 and HbE were carried out by quantification of HbA2 fraction following hemoglobin electrophoresis on cellulose acetate membrane (CAM) electrophoresis. The results of blood smear reading showed good intrarater agreement with kappa = 0.691 by the first rater and 0.634 by the second rater). The interrater agreement was high moderate to good (kappa = 0.567 - 0.728). The first reading by the first rater, the second reading by the first rater, the first reading by the second rater, and the second reading by the second rater showed sensitivities of 0.780, 0.780, 0.878, and 0.805 respectively; specificities of 0.708, 0.958, 0.542 and 0.792 respectively; positive predictive values of 0.820, 0.969, 0.766, and 0.868 respectively; and negative predictive values of 0.650, 0.719, 0.722, and 0.704 respectively. The peripheral blood smear has high sensitivity and specificity for diagnostic test of thalassemia syndrome.Key words: thalassemia syndrome - blood smear - hemoglobin electrophoresis - sensitivity and specificity -predictive value